Física de partículas: uma sequência didática para introdução do modelo padrão nas aulas de física do ensino médio - Silva, Erdelem Cris Gomes da (2024)
This dissertation aim to present the results of the research and implementation of a didactic sequence on the topic of the Standard Model of Particle Physics, based on Lev Vygotsky's learning theory, as also on the perspectives and challenges of teaching physics in the Amazonian context. Then taking into account these challenges inherent in the didactic transposition of such a complex subject, we sought to investigate which kind of approaches and strategies would be most appropriate for introducing and teaching the subject of particle physics in high school classes. This didactic sequence was designed to adapt to the new guidelines and norms established for secondary education by the National Common Curriculum Base (BNCC). In terms of teaching strategies, we tried to establish a dialogical approach, focusing on interdisciplinarity, emphasizing the process of building science and contributing to scientific literacy. The results, as well as the application of the educational product, proved to be satisfactory in terms of introducing the Standard Model into the context of physics classes.